Corporate integrity analysis via decision support system (DSS): evidence from Malaysian organization / Ayub Md Som ... [et al.] - Md Som, Ayub; Zainal, Rafidah; Mohamed, Nafsiah; Ali, Sherif Abdulbari (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM) Shah Alam, 2019)
With increased awareness towards ethics and integrity in Malaysia, the government through the Integrity Institute of Malaysia (IIM) had refined the scale of the original tool to reflect the local context with the development of the Corporate Integrity Assessment Questionnaire (CIAQ), which was later known as the Corporate Integrity System Malaysia (CISMTM). CISM was a mere questionnaire consisting of 12 dimensions with 214 questions. This study attempted to develop a prototype tool using an expert system methodology coupled with its own software architecture and computer programming by incorporating all elements in CIAQ, in order to analyze the current level of implementation stage of the CISMTM in an organization. For the purpose of this work, Organization A was included as a case study and the results showed that the organization had an integrity level of between 50% to 75%.  This clearly indicates that the organization is very likely in the right direction to implement ethics and integrity at the work place. Consequently, the tool is also able to provide some recommendations in the form of a decision support system for future improvements in the organization.